New additions of Spigelia (Loganiaceae) in Mexico - Islas-Hernández, C. Sofia; García, Rubí Bustamante; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2017)
Two new species of Spigelia (Loganiaceae) from the states of Guerrero and Estado de Mexico are described here. This species represents a case of convergence with a species native to South America, Spigelia nicotianiiflora. With this addition, Mexico reaches a total of 22 species of the genus, of which more than 50% are endemic or microendemic. This places the country as the second highest area of diversity after Brazil. A map of the distribution in Mexico and a dichotomous key for Spigelia species with white corollas are included.